2011
DOI: 10.1080/19317611.2011.611220
|View full text |Cite
|
Sign up to set email alerts
|

Masturbation Among Sexually Active Young Women in Croatia: Associations with Religiosity and Pornography Use

Abstract: The aim of this study was to examine the prevalence and correlates of masturbation among sexually active young women in Croatia. Data were collected in 2010 in a cross-sectional national probability study of youth sexuality. The analyses were based on a subsample of 416 female participants aged 18 to 25 years old. Sixty percent of the young women reported that they masturbate. Results from the multivariate logistic regression analysis indicate that the participants in the older age group (22 to 25 years old) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Future studies should examine whether the present findings may be generalized to these populations. Moreover, future studies may include masturbation frequency and additional measures of potential symptoms of PPU (e.g., craving for pornography use [86]) given their moderate-to-strong associations with PPU and pornography use frequency [29,87,88]. The network analytic approach should be used in clinical samples to enable the examination of the similarities and differences between the structure of symptoms identified in this community-based sample and clinical samples and to corroborate the clinical validity of the current study's findings.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…Future studies should examine whether the present findings may be generalized to these populations. Moreover, future studies may include masturbation frequency and additional measures of potential symptoms of PPU (e.g., craving for pornography use [86]) given their moderate-to-strong associations with PPU and pornography use frequency [29,87,88]. The network analytic approach should be used in clinical samples to enable the examination of the similarities and differences between the structure of symptoms identified in this community-based sample and clinical samples and to corroborate the clinical validity of the current study's findings.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…Moreover, masturbation was also linked to lower life satisfaction in men. These seemingly paradoxical associations might be related to the long-standing condemnation and stigmatization of masturbation that still elicits guilt, shame, and feelings of sexual inadequacy (Baćak & Štulhofer, 2011 ; Coleman, 2003 ; Hinchliff et al, 2018 ). Qualitative studies among younger adults indicate a substantial diversity of views on masturbation and provide some insights into the contradictious and conflicting experience of masturbation being both pleasurable and shameful (Hogarth & Ingham, 2009 ; Kaestle & Allen, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a Croatian study with 410 young women (between the ages of 18 and 25 years) revealed that 40% of participants reported that they never masturbated; of those who reported masturbation, 23% reported masturbating a few times per year or less frequently [18] . In urban China 13% of women reported any masturbation in the preceding year [19] while in an Australian study [20] , 35% of women had masturbated in the past year. A Finnish survey in 1992 reported that 77% of women had ever masturbated [21] and a Swedish study in 1996 found that 80% of women had evermasturbated [22] .…”
Section: Discussionmentioning
confidence: 93%
“…Also, the study of Herbenick et al [24] showed that masturbation was reported by more than half of women who were in a noncohabitating relationship compared with 12.2% of married women. This issue is further clarified in the work of Das et al [19] , who found that absence of a stable partner of women for periods over a week during the year was correlated with more masturbation.…”
Section: Discussionmentioning
confidence: 95%